Tree of heaven : poems - McKean, James, 1946 July 4- (Iowa poetry prize., 1995)
This second book by James McKean displays a large, dignified, and precise talent - McKean is always looking and reaching out to the difficult world, pulling it to him for examination. Although beginning with outward themes of travels and crossings, Tree of Heaven circles in the end to the journeys of the inner life: the struggle to understand, the ability to see, to suffer the trials of illness and death, to survive love and longing, learning when to leave things as they are, when to let go. McKean's accomplished voice is quiet but firm, at times full of wonder, exploring the personal and discovering what salvation there is in rhythm and words.